Summary actions CIAT Asia planning - International Center for Tropical Agriculture (2014)
SUMMARY OF CIAT ASIA TEAM PLANNING SESSION 19 – 21 FEBRUARY, HANOI Participants: Asia: Rod Lefroy, Keith Fahrney, Tassilo Tiemann, Adrian Bolliger, Tin Maung Aye, Kris Wyckhyus, Georgina Smith, Aparna Mani, Jonathan Newby, Sok Sophearith, Lao Thao, Ou Wenjun, Cu Thi Le Thuy, Giang Tuan Linh and Dindo Campilan (as an observer) HQ: Joe Tohme, Clair Hershey, Kayte Meola and André Zandstra